Nuclear Changes Features in Buccal Mucosa Smear of Adult Male Smokers Using Pappaniculou Staining - Yuktiana Kharisma; Raden Anita Indriyanti; Lelly Yuniarti; Noormartany Noormartany; Ismet Muchtar Nur; Yolanda Yenolinsky (Althea Medical Journal)
Background: Tobacco smoke contains a combination of chemicals that could be harmful to the buccal mucosa as the first part of the body that has been exposed. Damage to the buccal epithelial cells has the potential to become a malignant lesion. This study aimed to describe changes in the nuclear epithelial of the buccal mucosa using Pappaniculou staining as an indicator of mucosal damage in smokers.